Problematic aspects of interpretation of seismic signals induced by detonation of explosives - Pyra Józef; Twardosz Michał (E3S Web of Conferences, 2018)
The article presents problems concerning an interpretation of seismic signals registered in the ground and foundations of buildings which are induced by the detonation of explosives. In the course of blasting in opencast mines, harmful effects may occur. The primary impacts which usually occur are as listed, induced vibrations, airblast, acoustic wave and the flyrock. There are technical and technological methods to reduce them, but minimising one can enhance the impact of the other. Furthermore, impacts such as vibration, acoustic wave, and airblast may overlap - the additive effect, which might cause problems with the unambiguous identification and interpretation of the recordings. The paper presents the results of tests carried out on a laboratory scale of the detonation of varying weight explosives samples. Also, examples of seismic signals recorded during field measurements in the vicinity of open-pit mines are presented. Also, examples of seismic signals recorded during field measurements in the vicinity of open-pit mines are presented. These examples confirm doubt as to the applicability of PN-B-02170: 2016-12 to assess the effects of vibrations on the building structures in the event of a significant impact of the airblast.